Um framework de agentes de recomendação para sistemas Web - Medeiros, Danielle Gomes de Freitas (2011)
The World Wide Web has been consolidated over the last years as a standard platform to provide software systems in the Internet. Nowadays, a great variety of user applications are available on the Web, varying from corporate applications to the banking domain, or from electronic commerce to the governmental domain. Given the quantity of information available and the quantity of users dealing with their services, many Web systems have sought to present recommendations of use as part of their functionalities, in order to let the users to have a better usage of the services available, based on their profile, history navigation and system use. In this context, this dissertation proposes the development of an agent-based framework that offers recommendations for users of Web systems. It involves the conception, design and implementation of an object-oriented framework. The framework agents can be plugged or unplugged in a non-invasive way in existing Web applications using aspect-oriented techniques. The framework is evaluated through its instantiation to three different Web systems